Hybrid fractional fuzzy PID design for MPPT-pitch control of wind turbine-based bat algorithm - Maroufi, Oussama; Choucha, Abdelghani; Chaib, Lakhdar (Electrical engineering, 2020)
The power quality and protection enhancement of wind turbine becomes an important paramount. This requires a competitive controller with high performances. For this purpose, the paper presents a novel hybrid controller named fractional fuzzy PID (FFPID) strategy tunning with an efficient metaheuristic optimization bat algorithm (BA) for controlling the wind turbine equipped with permanent magnet synchronous generator (WT-PMSG). The main control objectives are to drive WT-PMSG for extracting the maximum power point (MPPT) in the low range of weather conditions and further to protect the wind turbine in high-wind region using pitch angle control. The performance of proposed strategy is analysed for all regions low–high wind speed disturbances. The obtained results are obviously proved that the optimal hybrid fractional-order fuzzy PID controller is highly better than the optimal classical PID, fuzzy PID (FPID) and fractional-order PID (FOPID) controllers in terms of response, overshoot and indices performances. Further, the WT-PMSG is effectively controlled at different conditions of wind velocities by the proposed scheme.